In vitro toxicity of glyphosate in Atlantic salmon evaluated with a 3D hepatocyte-kidney co-culture model - Søfteland, Liv Ingeborg Rosvoll; Olsvik, Pål Asgeir (Food and Chemical Toxicology, 2022)
publishedVersion